Lussazioni interfalangee e metacarpofalangee - Anania, V.; Chinni, C. (Lo Scalpello - Journal, 2018)
INTERPHALANGEAL AND METACARPOPHALANGEAL DISLOCATION OF FINGERS The term “dislocation” refers to the loss of contact of the articular surfaces of the phalanx joints. Very often the dislocation of a phalange is accompanied by injuries and involvement of the structures of adjacent soft tissues. These injuries are extremely common in those who practice sport and, in particular, in those sports activities that provide for anomalous and thraumatic contacts with a ball or contrasts with an opponent. In this short treatment we will examine the common joint dislocations interphalangeal and metacarpophalangeal of the fingers of the hand. For what concerns the pathology of the first finger, there is a great number of important lesions associated as fractures or lesions of ligaments (Stener); given the vastness and complexity of these diseases, that would require a separate treatment, we will confine ourselves to describing the “simple” dislocations of the first finger.